2016
DOI: 10.1016/j.foodchem.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Industrial scale microwave processing of tomato juice using a novel continuous microwave system

Abstract: This study evaluated the effect of an industrial scale continuous flow microwave volumetric heating system in comparison to conventional commercial scale pasteurisation for the processing of tomato juice in terms of physicochemical properties, microbial characteristics and antioxidant capacity. The effect against oxidative stress in Caco-2 cells, after in vitro digestion was also investigated. Physicochemical and colour characteristics of juices were very similar between technologies and during storage. Both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 36 publications
0
41
0
10
Order By: Relevance
“…These results showed that at a similar temperature (96 ± 2 °C) MWP maintained a better TAC than CP. In the same way, Stratakos et al reported that TAC in heated tomato juice was higher for MWP compared to CP at 85 °C. TAC depends on the extract and the intensity of heating applied to tomato samples .…”
Section: Resultsmentioning
confidence: 70%
“…These results showed that at a similar temperature (96 ± 2 °C) MWP maintained a better TAC than CP. In the same way, Stratakos et al reported that TAC in heated tomato juice was higher for MWP compared to CP at 85 °C. TAC depends on the extract and the intensity of heating applied to tomato samples .…”
Section: Resultsmentioning
confidence: 70%
“…Currently, this method is widely used in many laboratories around the world due to its simplicity of use [28][29][30]. Thus, the antioxidant activity of a vast range of compounds has been reported using this method.…”
Section: Comments About This Methodsmentioning
confidence: 99%
“…Quality of tomato and tomato products is affected by the use of heating during the industrial processing; color, viscosity and flavor are somewhat altered. Regarding the color, pigment degradation, and Maillard reactions can occur as well as ascorbic acid degradation (Stratakos, Delgado‐Pando, Linton, Patterson, & Koidis, ). Shi, Dai, Kakuda, Mittal, and Xue () reported significant loss in redness and color intensity of tomato puree after heating at 60–120°C for 1–6 hr.…”
Section: Conventional Thermal Processing As Current Practicementioning
confidence: 99%